2014
DOI: 10.1093/jxb/eru329
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of ripening among berries of the grape cluster reveals an altered transcriptional programme and enhanced ripening rate in delayed berries

Abstract: SummaryThe developmental programme of grape berries within a cluster is coordinated to synchronize their ripening. Altered transcriptional events and metabolite accumulation are responsible for the differential progress of ripening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 63 publications
10
48
1
Order By: Relevance
“…The variation in TSS throughout ripening of up to 5°Brix in Shiraz and around 3°Brix in Merlot highlights the large variation of post‐veraison berry ripening within a vineyard. Such heterogeneity of ripening berries even within one bunch can introduce considerable bias in molecular studies and other studies (Gouthu et al , Rienth et al , , Carbonell‐Bejerano et al ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation in TSS throughout ripening of up to 5°Brix in Shiraz and around 3°Brix in Merlot highlights the large variation of post‐veraison berry ripening within a vineyard. Such heterogeneity of ripening berries even within one bunch can introduce considerable bias in molecular studies and other studies (Gouthu et al , Rienth et al , , Carbonell‐Bejerano et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results in this study it cannot be concluded if the observed differences in TSS are because of a phenological shift of berries passing through veraison at different times, or if each berry goes through the ripening period at a different speed. To our knowledge, only one study has examined this problem systematically using a transcriptomic approach (Gouthu et al ). Their data led the authors to hypothesise that some berries lagged behind because of a phenological delay at veraison but that this was followed by a subsequent enhanced rate of ripening allowing these berries to ‘catch up’ with the others.…”
Section: Resultsmentioning
confidence: 99%
“…As a nonclimacteric fruit, grape development proceeds in two successive growth stages consisting of berry formation and ripening, separated by a lag phase (Figure 3; 33), and involves asynchronous ripening of individual berries within clusters during véraison and a transition from asynchrony to synchrony of clusters during post-véraison (55). Thus, the dynamics of compatible host-virus interactions at different tropic levels could be much more complex in long-living, clonally propagated grapevines due to chronic infections, tissue-specific expression patterns, species and cultivar level differences, and the influence of superimposing biotic and environmental variables during the crop season (96).…”
Section: Grapevine As a Hostmentioning
confidence: 99%
“…Genes associated to cell rescue, defense, death and aging were upregulated [19]. However, berry sampling in the latter study did not consider intra-cluster berry heterogeneity of ripening grapes [20] and/or the phenological shift generally caused by virus infections, which can introduce important biases in molecular studies and mask direct virus related transcriptomic effects [21][22][23]. For example, in the study of Vega et al (2011) [19], berry samples were drawn at 4 weeks' intervals throughout fruit development.…”
Section: Introductionmentioning
confidence: 99%